PERFORMANCE OF COMMON BEAN CULTIVARS IN DIFFERENT ENVIRONMENTS AND PLANT POPULATIONS (Colloquium Agrariae. ISSN: 1809-8215, 2024)
This study aimed to identify the most suitable plant populations, considering different environmental conditions, to express the yield potential of common bean cultivars released or in the process of releasing for regions not included in the initial release. Forty-four experiments were carried out from November 2016 to March 2019, encompassing wet, dry, and winter seasons, across the states of Goiás, Minas Gerais and Paraná. Five plant populations established at sowing (12, 18, 24, 30, and 36 plants m⁻²) were compared in a randomized block design with four replications, using the cultivars BRS FC310, BRS FC409, and BRSMG Uai. Across winter season experiments, the BRS FC310 cultivar consistently displayed higher yield than the others at all plant populations. In contrast, the BRSMG Uai cultivar exhibited the highest yield during the wet season. The maximum grain yields of the three cultivars were higher in the wet than in the winter season and obtained with higher plant populations. Cultivars BRS FC310, BRS FC409, and BRSMG Uai maximized grain yield with, respectively, 28.4, 25.4, and 26.2 plants m⁻² at harvest time in the wet season, and 20.4, 14.0, and 15.2 plants m⁻² in the winter season.